Winston Churchill as I Knew Him - Bonham Carter, Violet (London Pan Books Ltd., 1965)
This superb account of the public and private life of Winston Churchill makes a rare firsthand contribution to the history of an epoch and to the understanding of one of the 20th Century's most influential leaders. Violet Bonham Carter, daughter of Prime Minister H. H. Asquith, was Churchill's close personal friend for nearly sixty years. Her book focuses on the formative and crucial years from 1906 to 1916 that shaped his political style as well as his philosophy. It contains a vast amount of material that has never been previously published.
Include Notes, References and Index.
It is a biography.
Keywords: Prime ministers -- Great Britain -- Churchill, Winston, 1874-1965